2023
DOI: 10.3390/ijms242316585
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CONSTANS-like Proteins in Plant Flowering and Abiotic Stress Response

Bingqian Zhang,
Minghui Feng,
Jun Zhang
et al.

Abstract: The process of flowering in plants is a pivotal stage in their life cycle, and the CONSTANS-like (COL) protein family, known for its photoperiod sensing ability, plays a crucial role in regulating plant flowering. Over the past two decades, homologous genes of COL have been identified in various plant species, leading to significant advancements in comprehending their involvement in the flowering pathway and response to abiotic stress. This article presents novel research progress on the structural aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 164 publications
(203 reference statements)
0
1
0
Order By: Relevance
“…COL genes have been reported to be involved in many molecular regulation processes and plant growth development, including regulation of flowering time, photoperiodic responses and photomorphogenesis, stigma color and key roles in banana ( Musa nana ) fruit ripening ( Hassidim et al., 2009 ; Chen et al., 2012 ; Ordoñez-Herrera et al., 2018 ; Zhang et al., 2023a ). COL genes also involved in abiotic stress tolerance response, anthocyanin accumulation and plants carotenoid metabolism regulation ( Bai et al., 2019 ; Zhang et al., 2023a ). Besides, a zinc finger protein AdDof3 has been reported to interacted physically with the AdBAM3L promoter, regulating starch degradation in Kiwiruit ( Zhang et al., 2018 ), indicating a potential role in sugar metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…COL genes have been reported to be involved in many molecular regulation processes and plant growth development, including regulation of flowering time, photoperiodic responses and photomorphogenesis, stigma color and key roles in banana ( Musa nana ) fruit ripening ( Hassidim et al., 2009 ; Chen et al., 2012 ; Ordoñez-Herrera et al., 2018 ; Zhang et al., 2023a ). COL genes also involved in abiotic stress tolerance response, anthocyanin accumulation and plants carotenoid metabolism regulation ( Bai et al., 2019 ; Zhang et al., 2023a ). Besides, a zinc finger protein AdDof3 has been reported to interacted physically with the AdBAM3L promoter, regulating starch degradation in Kiwiruit ( Zhang et al., 2018 ), indicating a potential role in sugar metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth studies have revealed that phyA and phyB can temporally and dynamically regulate the protein levels of CONSTANT (CO), a B-box zinc finger protein, ensuring that plants recognize specific photoperiodic environments and thus precisely regulate flowering. In the morning, active phyB promotes CO protein degradation, leading it to lower levels of CO protein (Hajdu et al, 2015;Zhang et al, 2023b). In the afternoon phyA stabilizes the CO protein through the inhibition of the ubiquitin ligase activity of CULLIN 4 (CUL4)-DNA DAMAGE-BINDING PROTEIN 1 (DDB1) COP1/SPA .…”
Section: Regulation Of Plant Flowering Time By Phyamentioning
confidence: 99%
“…The DOFCOREZM/POLLENILELAT52 motif was found previously to be bound by CDF transcription factors, which have a dof domain identifying the DOFCOREZM/ POLLENILELAT52 motif (Imaizumi et al, 2005). CDFs regulate the expression of MYB60, SP5G by binding to the DOFCOREZM/POLLENILELAT52 motif in its promoters, and are involved in regulating potato tuberization and enhancement of activity in guard cells (Cominelli et al, 2011;Lehretz et al, 2019;Zhang et al, 2023). CDF transcription factors play important roles in plant growth and development (Jin et al, 2024).…”
Section: Interaction Of Llwox11 With Selected Motifs Actually Occurs ...mentioning
confidence: 99%